Sexual behavior among truck drivers - Rajiv Kumar Singh; Hari Shankar Joshi (Wolters Kluwer Medknow Publications, 2012)
A cross-sectional study was conducted on Lucknow highway in Bareilly district of Uttar Pradesh to study the knowledge of truck drivers about HIV transmission and prevention and to study the sexual behaviour of these drivers with reference to HIV/AIDS. Age, marital status, education, income, drinking alcohol, length of stay away from home, knowledge about transmission and prevention of HIV, and HIV-prone behavior of truck drivers were studied. Chi-square, mean, and SD were calculated. In all, 289 (97.6%) drivers had heard about HIV/AIDS. Only 242 (81.8%) were aware of HIV transmission by heterosexual route. Misconceptions such as HIV transmission by mosquito bites, living in same room, shaking hands, and sharing food were found. Out of 174 (58.8%) who visited Commercial Sex Workers (CSW), 146 (83.9%) used a condom. 38 (12.8%) visited more than 5 CSW in the last 3 months. Time away from home on the road, marital status, alcohol use, and income class were associated with visiting CSW. High-risk behavior was established in the study population. Safe sex and use of condoms need to be promoted among the truck drivers and better condom availability needs to be assured on highways.